A study of the miscibility of acrylic-based polymer blends - Nigel M. Hodgkinson (1991)
The work carried out in this study constitutes an investigation of the miscibility behaviour of a number of acrylic-based polymers with the high performance, fluoropolymer surface coating material Luniflon LF200. The aim was to find ways of improving the miscibility of LF200 with lower cost acrylic type surface coating materials. In order to more fully understand the mixing behaviour of LF200, blends were prepared with acrylic copolymers and a number of other polymeric materials. LF200 was found to be immiscible with a copolymer based on styrene (ST) and methacrylic acid (MAA), irrespective of the ST:MAA ratio. Miscible blends of LF200 were however, prepared with n-butyl acrylate (PBA) and polyethylene glycol (PEG) homopolymers, among others. [Continues.]